THE ROLE OF THE CHURCH IN POVERTY IN THE PERSPECTIVE OF GUSTAVO GUTIÉRREZ'S LIBERATION THEOLOGY - Hanna Masta Pasaribu; Riris Johanna Siagian (RADJA PUBLIKA, 2025)
This paper explores the issue and role of the church amidst poverty. Poverty is a crucial social issue that the church focuses on in its efforts to present the gospel and the kingdom of God. This paper uses the thoughts of Gustavo Guititerrez as a surgical tool to examine how the church should carry out its social function in addressing the issue of poverty. Poverty is seen as arising from structural injustice, and therefore the church must be present as part of its social responsibility. Therefore, Guititerrez offers a Liberation Theology perspective that synthesizes faith and action. This paper is qualitative in nature with a literature study approach. Therefore, data was obtained through a review of journals and books directly relevant to this research. This study found that the church must be present amidst the issue of poverty. The theological basis of the church's responsibility towards poverty lies in the recognition that God is on the side of the poor. The church is called to be a community of liberation—a fellowship that speaks not only of love but also lives in solidarity with the poor. According to Gutiérrez, the church's social service must be transformative, not merely charitable.